Improving mother’s knowledge for stunting prevention through customized health promotion during COVID-19 pandemic - Kalesaran, Angela Fitriani Clementine; Lotulung, Cindy Celine; Mandagi, Chreisye Kardinalia Francisca (BKM Public Health and Community Medicine, 2021)
Objective: This study aims to improve the knowledge of mothers of kids with stunting with different types of health promotion depending on the situation and restrictions during the COVID-19 pandemic. Method: This was a quasi-experimental research study with pre and post-test design. Fifty mothers from Wori District in North Sulawesi were included in the study. Twenty-five mothers received conventional health promotions in groups, and twenty-five mothers received health promotions one-on-one by home visits from healthcare workers. A questionnaire about mothers’ knowledge regarding stunting prevention was collected before and after the health promotion. Results: The number of mothers with a low level of knowledge was 36% before the health promotion, but then decreased to only 14% after the health promotion. There was a significant difference (p<.000) between pre and post-test regarding mother’s knowledge. Between groups receiving conventional health promotion and one-on-one health promotion, there were no significant differences regarding the knowledge of mothers after being given health promotion. Conclusion: Health promotion is an effective way to improve the knowledge of mothers with stunting kids. Health promotion one-on-one by the home visit is just as effective as health promotion in groups. Healthcare workers should be flexible and adaptive to the situation during the COVID-19 pandemic, so health promotion can always be delivered.